(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present study entitled “A study of educational status of scheduled caste woman in India”. The scheduled caste who are classified as untouchables appear to exist at the bottom of India`s upper castes. Scheduled caste women are traditionally depressed and neglected in Indian society. They also remain at the bottom of economic hierarchy, having no land of the own. Education is the only weapon through which the status of the scheduled caste women in society can be improved. Governmental and non-governmental agencies have made a lot of efforts, provisions and reservation for the improvement of scheduled caste women.But even today scheduled caste a woman is designated as “disadvantaged group”.